Risk stratiﬁcation using gated stress myocardial perfusion imaging: comparison between patients with and without sexual dysfunction. Issue 1 (January 2016) - Tan, Yusuf Ziya; Ozdemir, Semra; Bekler, Adem; Akbas, Alpaslan; Gencer, Meryem; Celik, Fatmanur
Abstract : Sexuality is an indispensable part of life. When a problem is encountered related to this topic, the quality of life is negatively affected. Therefore, every problem related to sexuality is extremely private and important to an individual. This study aims to investigate the use of myocardial perfusion scintigraphy (MPS) for advanced assessment of patients with known or suspected coronary artery disease, cardiovascular disease, and in the intermediate risk group for SD. The study included 250 patients (150 male, 100 female, mean age 54±12.10) sent by the Cardiology Clinic to the Nuclear Medicine Clinic for MPS due to suspected cardiovascular disease (CVD). The questionnaire study was applied by two methods as face-to-face interviews or online. Data on sociodemographic characteristics and cardiovascular diseases together with risk factors for sexual activity were collected using a general information form. Patients were divided into three categories of risk depending on major risk factors for cardiovascular diseases: low, intermediate, and high risk. On comparing the risk scores between the groups, it was seen that there was a statistically clear reduction in the intermediate risk group of patients with SD according to MPS scoring. MPS is a cost-effective, reliable, and accurate non-invasive diagnostic method necessary for routine use to assess cardiovascular disease and in the intermediate risk group for SD.